Structure and tribomechanical properties of extrudable ultra-high molecular weight polyethylene composites fabricated by 3D-printing; AIP Conference Proceedings; Vol. 2141 : Oil and Gas Engineering (OGE-2019) - Panin S. V. Sergey Viktorovich; Buslovich D. Dmitry; Kornienko L. A. Lyudmila Aleksandrovna; Aleksenko V. O. Vladislav Olegovich; Dontsov (Doncov) Yu. Yuriy Vladimirovich; Ovechkin B. B. Boris Borisovich (2019, 2019)
Title screen